Auditoría en seguridad vial tramo Pereira - Alcalá abscisas Km 5+200 - Km 11+200 entre los departamentos de Risaralda y valle del cauca (2022)
his document contains the development of the Safety Audit, section Pereira - Alcalá abscisas Km: 5+200 - Km: 11+200 to the variables: barriers, geometric design of the road and signage, to establish its condition against the road actors that they circulate through it, for its execution they were taken as a methodology.